Count the ways [compact disc, unabridged] : a novel - Maynard, Joyce, 1953- (Harper Audio, 2021)
After falling in love in the last years of the 1970s, Eleanor and Cam follow their dream of raising three children on a New Hampshire farm. Theirs is a seemingly idyllic life of summer softball games and Labor Day cookouts, snow days and skating on the pond. But when a tragic accident permanently injures the family's youngest child, Eleanor blames Cam. Her inability to forgive him leads to a devastating betrayal: an affair with the family babysitter that brings about the end of their marriage. Over the decades that follow, the five members of this fractured family, and the many others who make up their world, make surprising discoveries and decisions that occasionally bring them together, and often tear them apart. As the story follows the family from the days of illegal abortion and the draft through the early computer age, the Challenger explosion, the AIDS epidemic, the early awakenings of the #MeToo era, and beyond, through the gender transition of one of the children and another's choice to cease communication with her mother, the family is forced to confront essential, painful truths of its past, and finds redemption in the face of unanticipated disaster.